The effect of inhibiting hindbrain A2 noradrenergic neurons by 6-Hydroxydopamine on lipopolysaccharide-treated male rats autistic animal model - Hussain N. Alhamami; Abdullah M. Albogami; Mohammad M. Algahtani; Mohammed Alqinyah; Wael A. Alanazi; Fawaz Alasmari; Khalid Alhazzani; Ahmed Z. Alanazi; Yasseen A. Alassmrry; Abdullah S. Alhamed (Saudi Pharmaceutical Journal, 2024)
Autism spectrum disorder (ASD) is a complex neurodevelopmental illness that often emerges in early childhood. The incidence of ASD has shown a notable rise in recent years. ASD is defined by deficits in social communication, and presence of rigid and repetitive behaviors and interests. The underlying mechanisms of ASD remain elusive. Multiple studies have documented the presence of neuroinflammation and increased levels of inflammatory cytokines, specifically, IL-6, TNF, and NF-κB, in various brain regions, including the prefrontal cortex (PFC) and hippocampus in individuals with ASD. Noradrenergic neurons play a crucial role in brain development and the regulation of motor, behavioral, and memory functions. This study sought to examine the impact of intracerebroventricular (icv.) injection of the neurotoxin, 6-hydroxydopamine (6-OHDA), in the caudal dorsal vagal complex A2 neurons on various neuroinflammatory pathways at the hippocampus and PFC in valproic acid (VPA) autistic animal model. This was done in conjunction with an intraperitoneal (i.p.) injection of Lipopolysaccharides (LPS) in animal models with VPA-induced autism. We specifically examined the impact of the caudal fourth ventricle 6-OHDA icv. injection and LPS (i.p.) injection on self-grooming behavior. We measured the mRNA expression of IL-6, TNF-a, and NF-κB using qRT-PCR, and the protein expression of COX-2, GPX-1, p-AMPK, and AMPK using western blot analysis. The self-grooming activity was considerably higher in the combined treatment group (6-OHDA icv. + LPS i.p.) compared to the control group. A substantial increase observed in the expression of IL-6, TNF-α, and NF-κB genes in the PFC of the treatment group that received icv. Administration of 6-OHDA, compared to the control group. The VPA-autism rats that received the combo treatment exhibited a slight increase in the expression level of NF-κB gene in the hippocampus, compared to the control group. At the PFC, we noticed a substantial drop in the expression of the antioxidant protein GPX-1 in the group that received the combo treatment compared to the control group. Our data investigates a novel aspect that the 6-OHDA-induced inhibition of hindbrain A2 neurons could be influencing the neuroinflammatory pathways in the PFC and hippocampus of autistic animal models.